Interactive effect of reduced pollen availability and Varroa destructor infestation limits growth and protein content of young honey bees - van Dooremalen, C.; Stam, E.; Gerritsen, L.; Cornelissen, B.; van der Steen, J.; van Langevelde, F.; Blacquière, T. (Journal of insect physiology, 2013)
[Display omitted] ► Varroa destructor and reduced pollen availability affected Apis mellifera. ► Both factors reduced body weight and protein content of the abdomen in young bees. ► Retarded growth due to V. destructor could not be compensated for by ample pollen. ► A lack of protein build-up could also not be compensated for by ample pollen. ► We contribute to understanding the multifactorial origin of honeybee losses.. Varroa destructor in combination with one or more stressors, such as low food availability or chemical exposure, is considered to be one of the main causes for honey bee colony losses. We examined the interactive effect of pollen availability on the protein content and body weight of young bees that emerged with and without V. destructor infestation. With reduced pollen availability, and the coherent reduced nutritional protein, we expected that V. destructor infestation during the pupal stage would have a larger negative effect on bee development than without infestation. Moreover, when raised with ample pollen available after emergence, infested pupae were expected not to be able to compensate for early losses due to V. destructor. We found that both V. destructor infestation and reduced pollen availability reduced body weight, abdominal protein level, and increased the head to abdomen protein ratio. The availability of pollen did indeed not result in compensation for reduced mass and protein content caused by V. destructor infestation in young bees after 1week of their adult life. Both V. destructor and nutrition are top concerns for those studying honey bee health and this study demonstrates that both have substantial effects on young bees and that ample available pollen cannot compensate for reduced mass and protein content caused by V. destructor parasitism.